Physicochemical Properties of Cheddar Cheese made from Citrus reticulata Blanco Crude Flowers Extract - Usman Mir Khan; Ishtiaque Ahmad; Saima Inayat; Hafiz Muhammed Arslan Amin; Zeliha Selamoglu (Turkish Journal of Agriculture: Food Science and Technology)
Citrus reticulata Blanco crude flowers extracts (CFE) at four different concentrations (1, 2, 3 and 4%, v/v) were used as natural milk coagulant instead of rennet to apply for Cheddar cheese making from buffalo milk. The physicochemical properties of Cheddar cheeses were compared with cheese made with 0.002% (v/v) rennet (control cheese). Physicochemical properties of Cheddar cheese showed that cheese made with 1% and 2% of CFE had a crumbly and slightly softer texture/appearance. While cheeses containing 3 and 4% crude flowers extracts had semi-hard texture/appearance of curd similar to rennet added cheese. Protein analysis shows that crude flowers extracts made cheese had significantly higher protein content than control. The Cheddar cheese with 3% and 4% CFE were preferred by panelists instead of 1% and 2% CFE for their taste, texture/appearance and overall acceptability. Conclusively, crude flowers extracts coagulated Cheddar cheese fulfills the compositional requirement with acceptable organoleptic characteristics and at the same time provides nutritional health benefits.